The Role of Artificial Intelligence in Shaping International Law and Foreign Policy: A Qualitative Study on State Behavior and Global Norms - Shahzad, Shahbaz Ahmed; Aziz, Basit; Mehdi, Tabinda (ACADEMIA International Journal for Social Sciences, 2025)
Artificial intelligence (AI) has taken the center stage of political attention across the world, and is becoming more and more influential on how states practice power, or policy formulate, as well as negotiate international rules. The paper will discuss the future of international law and foreign policy through the impact of AI, especially its connection to the state behavior and the development of international standards. The paper is based on the application of a qualitative research design as it is a synthesis of the doctrinal analysis of international legal tools and a thematic study of existing theoretical literature and the comparative analysis of approaches of the United States, China, and the European Union in developing AI. The results indicate AI has turned into a strategic resource, which has increased geopolitical competition, is driving military innovation, and changing diplomatic and information practice, such as surveillance and disinformation. Simultaneously, AI has provoked the creation of new soft-law and regional policies, including the OECD AI Principles, the Recommendation on the Ethics of AI by UNESCO, or the proposed Artificial Intelligence Act to the European Union. Nonetheless, major loopholes still exist with the implementation of current international law in AI, specifically attribution and accountability, autonomous weapons, governance of data, and human rights safeguards. The article claims that the present international governance delineation of AI is divided, and very much infected by rival political and regulatory frameworks. It finds that there is the necessity of more concerted, integrative, and binding international action to make sure that AI promotes rather than subverts international peace, the rule of law, and the core human rights.